Marine oxygen production and open water supported an active nitrogen cycle during the Marinoan Snowball Earth. Issue 1 (December 2017) - Johnson, Benjamin; Poulton, Simon; Goldblatt, Colin
Abstract The Neoproterozoic Earth was punctuated by two low-latitude Snowball Earth glaciations. Models permit oceans with either total ice cover or substantial areas of open water. Total ice cover would make an anoxic ocean likely, and would be a formidable barrier to biologic survival. However, there are no direct data constraining either the redox state of the ocean or marine biological productivity during the glacials. Here we present iron-speciation, redox-sensitive trace element, and nitrogen isotope data from a Neoproterozoic (Marinoan) glacial episode. Iron-speciation indicates deeper waters were anoxic and Fe-rich, while trace element concentrations indicate surface waters were in contact with an oxygenated atmosphere. Furthermore, synglacial sedimentary nitrogen is isotopically heavier than the modern atmosphere, requiring a biologic cycle with nitrogen fixation, nitrification and denitrification. Our results indicate significant regions of open marine water and active biologic productivity throughout one of the harshest glaciations in Earth history. Snowball Earth glaciations were some of the most extreme climate events in Earth history, and are temporally linked to major biogeochemical changes. Here, using geochemical proxies, the authors show that during the Marinoan glaciation, there was likely open water, active oxygen production, and nitrogen cycling.